Analytical Study of Oil Recovery on Gas Lift and ESP Methods - Setiawan, Yudi (Universiti Teknologi PETRONAS, 2013)
Hydrocarbons usually flow from the wellbore to the surface immediately with the help of natural drive mechanism. But, when the pressure from natural reservoir drive falls to the point in which the well cannot produce on its own, a various types of oil recovery methods are taken into action. Artificial lift is one of the most widely used in oil recovery methods. However, artificial lift is very wide and varied. Furthermore, selection of this artificial lift method will maximize the potential oil recovery from developing oil field. Gas lift and ESP (Electrical Submersible Pump) are widely used in the oil and gas operation. As a result, a thorough evaluation of this artificial lift method is very crucial for long term profitability in a long run. Thus, this study aims an in-depth analysis of the behavior of oil well which requires gas lift and ESP to deliver an optimized oil production. This will be based on steady state simulation of oil producing well in Sarawak field, courtesy of PETRONAS Carigali Sdn. Bhd by using PROSPER software. Along with the simulation results, a comparison between gas lift and ESP will be identified and analyzed. This will result to a generic selection strategy of gas lift and ESP methods optimization.